Correction: QSAR without borders. (22nd May 2020) - Muratov, Eugene N.; Bajorath, Jürgen; Sheridan, Robert P.; Tetko, Igor V.; Filimonov, Dmitry; Poroikov, Vladimir; Oprea, Tudor I.; Baskin, Igor I.; Varnek, Alexandre; Roitberg, Adrian; Isayev, Olexandr; Curtarolo, Stefano; et al.
Abstract : Correction for 'QSAR without borders' by Eugene N. Muratov et al., Chem. Soc. Rev., 2020, DOI: ; 10.1039/d0cs00098a .